2020
DOI: 10.1532/hsf.2731
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Levosimendan Versus IABP in Patients with Poor Left Ventricular Function Undergoing Coronary Artery Bypass Graft Surgery

Abstract: Objectives: The aim of this study was to compare the use of levosimendan versus intra-aortic balloon pump (IABP) in patients with poor left ventricular function undergoing coronary artery bypass grafting (CABG) with ejection fraction less than 35%. Methods: Between February 2016 and March 2019, a prospective randomized study was performed on a group of 279 consecutive patients with left ventricular ejection fraction < 35%, who underwent elective CABG without concomitant procedures. These patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
(16 reference statements)
4
1
0
Order By: Relevance
“…This result agrees with Mate et al, [11] which showed that length of ICU stay in levosimendan group was 4.4±0.2 days and 6.5±0.1 days with IABP and this was statistically significant (P value <0.001). This result also agrees with Omar et al, [13] which showed that length of ICU stay in levosimendan group was 4.4±0.8 days and 5.2±0.9 days with IABP and this was statistically significant (P value <0.005).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This result agrees with Mate et al, [11] which showed that length of ICU stay in levosimendan group was 4.4±0.2 days and 6.5±0.1 days with IABP and this was statistically significant (P value <0.001). This result also agrees with Omar et al, [13] which showed that length of ICU stay in levosimendan group was 4.4±0.8 days and 5.2±0.9 days with IABP and this was statistically significant (P value <0.005).…”
Section: Discussionsupporting
confidence: 92%
“…These results can be explained by frequent complications of IABP as an invasive procedure like bleeding and infection or anticoagulation related like serious bleeding or thrombocytopenia or HIT as shown in table 4. That finding agrees with Severi et al [12] and Omar et al [13] where P value was 0.3 and 0.6 respectively when mortality was compared between two groups. This finding disagrees with Treskatsch et al [14] which enrolled 159 patients with low cardiac output syndrome post-operative to assess the effects on postoperative outcome of levosimendan and showed that significant reduction of mortality with levosimendan compared with conventional therapy (P value = 0.04).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The mortality rate among IABP and Levosimendan group in current study, was 10% and 5% respectively with no statistically significant difference between them (p>0.05). In a line with current findings, primary results from a randomized clinical trial by Omar et al 18 study conducted in 279 consecutive patients with LVEF < 35% undergoing CABG surgery identified no significant difference in mortality rate between patients who received 0.1 μg/kg/min levosimendan for 24 h and those assigned to an IABP, although the length of ICU stay was shorter in the levosimendan group (4.4 vs 5.2 days; p = 0.05).…”
Section: Discussionsupporting
confidence: 88%
“…Primary results from a randomized clinical trial conducted in 279 consecutive patients with LVEF < 35% undergoing CABG surgery identified no significant difference in mortality rate between patients who received 0.1 μg/kg/min levosimendan for 24 h and those assigned to an IABP, although the length of ICU stay was shorter in the levosimendan group (4.4 vs 5.2 days; p = 0.05) [ 12 ]. The use of levosimendan in high-risk cardiac patients was thus comparable to that of an IABP, with implications for cost of care.…”
Section: Postoperative Settingsmentioning
confidence: 99%